The analysis of the medical tourism expansion policy in Taiwan: a policy analysis using Kingdon's multiple streams - Ying-Ju Yu; Nicole Huang; Hsu-Sung Kuo (BMC, 2024)
Abstract Background Since 2006, Taiwan has actively pursued the development of its medical tourism industry. In 2013, the government sought to bolster this sector by integrating medical tourism into the Free Economic Pilot Zones. Despite narrowly missing the mark, the initiative failed to materialize into law. This qualitative study endeavors to discern the pertinent factors influencing the agenda-setting process for incorporating medical tourism into the Free Economic Pilot Zones in Taiwan. Methods A comprehensive examination of policies concerning the legitimation of medical tourism within the Free Economic Pilot Zones was undertaken through semi-structured interviews and a thorough review of policy documents. Key informants were strategically selected using purposive and snowball sampling techniques. Thematic analysis was applied to scrutinize the amassed data and organize it within the framework of Kingdon's multiple streams. Results In the problem stream, increasing financial strains and cost containment pressures under the National Health Insurance program have long driven health care providers to seek further opportunities in medical tourism. The existing barriers to expanding medical tourism in Taiwan included diplomatic tensions (specifically cross-strait relations), public concerns about commercialization of medical care and reduced their access to care, and legal and language barriers. Within the policy stream, factors such as franchise fees to support national health insurance, limited number of demonstration medical tourism sites and services allowed, the allowance of foreign medical personnel, regulations governing domestic physicians, the importance of demonstration, regulation, and accreditation, as well as restrictions on investment from China, were emphasized. The politics stream highlights factors such as governmental support, opposition from opposing parties, public concerns and critics from academia and non-governmental organizations, and skepticism from medical faculties. Conclusion Acknowledging the recognized challenges in enacting the medical tourism provision of the Free Economic Pilot Zones Special Act and emphasizing the political will of leadership, a viable policy solution remained elusive. Although a window of opportunity existed for the passage of the bill, it waned as public concerns sidelined the issue from the national agenda. The Taiwan case underscores the necessity for meticulous consideration of issues, proposed solutions, and political dynamics to achieve successful policy enactment.